2008
DOI: 10.1093/jee/101.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Screening Hybrid Poplar Clones for Susceptibility to Cryptorhynchus lapathi (Coleoptera: Curculionidae)

Abstract: The poplar-and-willow borer, Cryptorhynchus lapathi (L.) (Coleoptera: Curculionidae), is a wood-boring pest of economic importance in irrigated hybrid poplar (Populus spp.) farms in eastern Washington and Oregon. There is no practical insecticide control tactic against either the larval or adult stage of C. lapathi. To assess variability in C. lapathi toward clone preference, we initiated a no-choice study on 180 caged trees that consisted of five clones in a randomized complete block design. C. lapathi was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Using Dyar's rule, six instars occur for development of E. brandti larvae (Table 2). This is similar to the closely related species Cryptorhynchus lapathi (L.) (Coleóptera: Curculionidae), which had a mean growth ratio of 0.73 (Hannon et al 2008). Duration of the larval stage was 110 ± 15.0 d. The duration of each individual instar was not able to be determined due to the limitations of sampling for lai-vae under the bark ofthe billets.…”
Section: Adult Morphologicalsupporting
confidence: 68%
See 1 more Smart Citation
“…Using Dyar's rule, six instars occur for development of E. brandti larvae (Table 2). This is similar to the closely related species Cryptorhynchus lapathi (L.) (Coleóptera: Curculionidae), which had a mean growth ratio of 0.73 (Hannon et al 2008). Duration of the larval stage was 110 ± 15.0 d. The duration of each individual instar was not able to be determined due to the limitations of sampling for lai-vae under the bark ofthe billets.…”
Section: Adult Morphologicalsupporting
confidence: 68%
“…The data indicate that E. brandti had six stadia or "larval groupings." Studies by Hannon et al (2008), on the closely related poplar-and-willow borer [ Cryptorhynchmlapathi (L.) (Coleóptera: Curculionidae) ], found similar results in field-collected beetles and identified six larval groupings. The entire time required for E. brandti larval development from first instar to pupation was «»110.0 ± 15.0 d.…”
Section: Discussionmentioning
confidence: 75%
“…The authors concluded that this effect was due to antibiosis found in the resistant clones. Hannon, Kittelson, Eaton, and Brown (2008) also reported arrested larval development in Populus maximowiczii clones.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, the hybrid P. deltoides × P. balsamifera, descending from two American parents, showed no infestation, highlighting the complexity of genetic influences on pest resistance. The experience of Hannon et al [29] suggests that hybrids with P. deltoides × P. nigra parentage are more resistant to stem borers than P. trichocarpa × P. deltoides or P. trichocarpa × P. nigra parentage.…”
Section: A×tmentioning
confidence: 99%